(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The aim of the research is to study the level of social anxiety and self-compassion, and to study the relationship between social anxiety and self-compassion among the members of the research sample, and determine the significance of differences in social anxiety and self-compassion according to gender variables, the sample consisted of (30) Adolescents stuttering, (16) males and (14) females, and The self-compassion scale was used by Christine Neff (2003) and the social anxiety questionnaire prepared by the researcher, and it was applied in the city of Damascus,the research reached the following results: the presence of a high level of social anxiety, a medium level of self-compassion, and a negative correlation between social anxiety and self-compassion, the existence of differences Statistical significance between the sample members in social anxiety according to the gender variable in favor of females, the existence of differences Statistical significance between the sample members in self-compassion according to the gender variable in favor of female, In addition, there were no statistically significant differences between the sample members in the severity of stuttering according to the gender variable., in addition to the presence of significant in the interaction between the variables of self-compassion and gender and the severity of stuttering with the social anxiety variable.